1990
DOI: 10.3168/jds.s0022-0302(90)79005-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size of Forage and Rumen Cannulation upon Chewing Activity and Laterality in Dairy Cows

Abstract: Three ruminally cannulated Holstein dairy cows housed in free stalls (with .7% slope) were fed three total mixed rations, differing in silage particle size, in a 3 x 3 Latin square design. Observations on cow behavior were made every 5 min during 24 h for each of three periods. Additional observations of six cows (three intact, three cannulated) housed under identical conditions yielded information concerning recumbent rumination activity and laterality. Results indicated that decreasing particle size of forag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 13 publications
2
34
1
Order By: Relevance
“…Most rumination occurs at night when cows are at rest, but cattle also ruminate throughout the day when not interrupted by management such as feeding and milking (Grant et al, 1990;Dado and Allen, 1994;Paudyal et al, 2016). Schirmann et al (2012) reported that rumination time peaked approximately 4 h after feeding and that periods of rumination were also associated with time spent lying down.…”
Section: Factors Affecting Ruminating Behaviormentioning
confidence: 99%
“…Most rumination occurs at night when cows are at rest, but cattle also ruminate throughout the day when not interrupted by management such as feeding and milking (Grant et al, 1990;Dado and Allen, 1994;Paudyal et al, 2016). Schirmann et al (2012) reported that rumination time peaked approximately 4 h after feeding and that periods of rumination were also associated with time spent lying down.…”
Section: Factors Affecting Ruminating Behaviormentioning
confidence: 99%
“…Several characteristics of forage affect the intake of ruminants, particularly the content of vegetable fiber such as cellulose and lignin [11]–[13]. Cellulose is accessible to enzymes that normally digest carbohydrates, whereas lignin has high chemical-degradation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Grant et al, 1990a and1990b;Beauchemin and Yang, 2005), most of the studies used single forages in the diet, mainly silages with a relatively low dietary fiber content (23% to 32% NDF on dry matter (DM) basis). In a meta-analysis, Tafaj et al (2007) concluded that digestive effects of PS should be -E-mail: smnasrolahi@gmail.com considered in relation with particularly forage NDF in the diet.…”
Section: Introductionmentioning
confidence: 99%